The effect of DNA-binding proteins on insertion sequence element transposition upstream of the bgl operon in Escherichia coli - Kopkowski, Peter W.; Zhang, Zhongge; Saier, Milton H. (Frontiers in Microbiology, 2024)
The bglGFB operon in Escherichia coli K-12 strain BW25113, encoding the proteins necessary for the uptake and metabolism of β-glucosides, is normally not expressed. Insertion of either IS1 or IS5 upstream of the bgl promoter activates expression of the operon only when the cell is starving in the presence of a β-glucoside, drastically increasing transcription and allowing the cell to survive and grow using this carbon source. Details surrounding the exact mechanism and regulation of the IS insertional event remain unclear. In this work, the role of several DNA-binding proteins in how they affect the rate of insertion upstream of bgl are examined via mutation assays and protocols measuring transcription. Both Crp and IHF exert a positive effect on insertional Bgl + mutations when present, active, and functional in the cell. The mechanisms of how these two proteins may cause this effect are discussed. Our results characterize IHF's effect in conjunction with other mutations, show that IHF's effect on IS insertion into bgl also affects other operons, and indicate that it likely exerts its effect by binding to and altering the DNA conformation of IS1 and IS5 in their native locations, rather than by directly influencing transposase gene expression. In contrast, the cAMP-CRP complex acts directly upon the bgl operon by binding upstream of the promoter, presumably altering local DNA into a conformation that enhances IS insertion.